2016
DOI: 10.1111/mmi.13328
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression regulatory networks in Trypanosoma brucei: insights into the role of the mRNA‐binding proteome

Abstract: Control of gene expression at the post-transcriptional level is essential in all organisms, and RNA-binding proteins play critical roles from mRNA synthesis to decay. To fully understand this process, it is necessary to identify the complete set of RNA-binding proteins and the functional consequences of the protein-mRNA interactions. Here, we provide an overview of the proteins that bind to mRNAs and their functions in the pathogenic bloodstream form of Trypanosoma brucei. We describe the production of a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
207
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(216 citation statements)
references
References 84 publications
7
207
2
Order By: Relevance
“…For example, the artificial tethering of a REG9 . 1 -lambda-N peptide fusion to a reporter gene 3’UTR bearing a BoxB lambda-N recognition sequence resulted in reporter gene repression [27, 36] consistent with the repressive effect we observed on ESAG9 transcripts. Intriguingly, however, we found that the overall abundance of REG9 .…”
Section: Resultssupporting
confidence: 78%
“…For example, the artificial tethering of a REG9 . 1 -lambda-N peptide fusion to a reporter gene 3’UTR bearing a BoxB lambda-N recognition sequence resulted in reporter gene repression [27, 36] consistent with the repressive effect we observed on ESAG9 transcripts. Intriguingly, however, we found that the overall abundance of REG9 .…”
Section: Resultssupporting
confidence: 78%
“…PRO , but not TbPRMT1 ENZ , is reportedly phosphorylated (8,45), bound to mRNA (46), and trafficked to stress granules in starved trypanosomes (47). This suggests that TbPRMT1 PRO could be, in certain situations, operating independently of TbPRMT1 ENZ , possibly as a homodimer (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Correspondingly, results from a high-throughput RNAi screen indicated that ZC3H32 is required for proliferation of bloodstream forms, but not procyclic forms [13]. CCCH zinc finger domains usually bind RNA, and indeed, ZC3H32 was detected in a mass spectrometry analysis of proteins that cross-link to polyadenylated RNA in bloodstream forms in vivo [14]. …”
Section: Introductionmentioning
confidence: 99%
“…We speculated that recruitment of the MKT1 complex by ZC3H32 should result in stablization of any mRNAs that are associated with ZC3H32. However, when ZC3H32 was artificially attached to a reporter in a "tethering" screen, results suggested instead that expression was suppressed [14]. …”
Section: Introductionmentioning
confidence: 99%